Changes in water characteristics and pore distributions in loam soil under the coexistence of microplastics and salts - Xuguang Xing; Liuchang Su; Dongwei Li; Fengyue Zhao; Weihua Wang (Geoderma)
Farmland salinization and microplastics (MPs) pollution are increasing worldwide, posing threats to environmental health and accelerating land degradation. In the context of the global ecological challenges of land degradation and pollution, clarifying the interactions between MPs and salts is beneficial for land development and sustainable management. We measured the hydraulic parameters and calculated the water characteristics and pore distributions of the soils with different salinities (i.e., 0, 1, 3, and 5 g/kg) and MPs mixing contents (i.e., 0, 5, 10, and 30 g/kg). Results indicated that MPs generally reduced the soil saturated hydraulic conductivity, but the increased soil salinity weakened the effects of MPs on it. According to the soil water retention curves, MPs weakened the water-holding capacity, with a greater impact in non-saline soil than in saline soil. In non-saline soil, MPs caused the saturated water content to decrease by 4.6 %–8.1 %. In addition, MPs reduced the field capacity and wilting coefficient of both soils. The effect of MPs on available water was greater in non-saline soil than in saline soil. Furthermore, MPs reduced the total porosity of both soils. However, MPs had no significant effect on pore distribution in non-saline soil, whereas, in saline soil, MPs increased the proportion of micro pores and small pores but decreased the proportion of macro pores and voids. We determined that, in addition to changing the pore distribution, MPs and salts changed the water characteristics through hydrophobicity and ionic interactions, respectively. Our findings provide evidence of the influence of MPs on the physical properties of saline soil, highlighting the need for improved regulation and land management in plastic-polluted soil–crop systems.